Seasonal variability in the fertilization rate of women undergoing assisted reproduction treatments - De Almeida Ferreira Braga, Daniela Paes; Setti, Amanda; Savio Figueira, Rita de Cassia; Iaconelli, Assumpto; Borges, Edson [UNESP] (Informa Healthcare, 2012)
The objective of this study was to evaluate whether seasonality affects human-assisted reproduction treatment outcomes. For this, 1932 patients undergoing intracytoplasmic sperm injection (ICSI) were assigned to a season group according to the day of oocyte retrieval: winter (n = 435), spring (n = 444), summer (n = 469) or autumn (n = 584). Analysis of variance was used to compare the ICSI outcomes. The fertilization rate was increased during the spring (winter: 67.9%, spring: 73.5%, summer: 68.7% and autumn: 69.0%; p < 0.01). In fact, a nearly 50% increase in the fertilization rate during the spring was observed (odds ratio 1.45, confidence interval 1.20-1.75; p < 0.01). The oestradiol concentration per number of oocytes was significantly higher during the spring (winter: 235.8 pg/mL, spring: 282.1 pg/mL, summer: 226.1 pg/mL and autumn: 228.7 pg/mL; p = 0.030). This study demonstrates a seasonal variability in fertilization after ICSI, where fertilization is higher during the spring than at any other time.
Keywords: Fertilization; ICSI; oestradiol; photoperiod; seasonality